Dysregulation of IL-17/IL-22 Effector Functions in Blood and Gut Mucosal Gamma Delta T Cells Correlates With Increase in Circulating Leaky Gut and Inflammatory Markers During cART-Treated Chronic SIV Infection in Macaques - Walker, Edith M.; Slisarenko, Nadia; Gerrets, Giovanni L.; Grasperge, Brooke F.; Mattison, Julie A.; Kissinger, Patricia J.; Welsh, David A.; Veazey, Ronald S.; Jazwinski, S. Michal; Rout, Namita (Frontiers in Immunology, 2021)
HIV-associated inflammation has been implicated in the premature aging and increased risk of age-associated comorbidities in cART-treated individuals. However, the immune mechanisms underlying the chronic inflammatory state of cART-suppressed HIV infection remain unclear. Here, we investigated the role of γδT cells, a group of innate IL-17 producing T lymphocytes, in the development of systemic inflammation and leaky gut phenotype during cART-suppressed SIV infection of macaques. Plasma levels of inflammatory mediators, intestinal epithelial barrier disruption (IEBD) and microbial translocation (MT) biomarkers, and Th1/Th17-type cytokine functions were longitudinally assessed in blood and gut mucosa of SIV-infected, cART-suppressed macaques. Among the various gut mucosal IL-17/IL-22-producing T lymphocyte subsets including Th17, γδT, CD161+ CD8+ T, and MAIT cells, a specific decline in the Vδ2 subset of γδT cells and impaired IL-17/IL-22 production in γδT cells significantly correlated with the subsequent increase in plasma IEBD/MT markers (IFABP, LPS-binding protein, and sCD14) and pro-inflammatory cytokines (IL-6, IL-1β, IP10, etc.) despite continued viral suppression during long-term cART. Further, the plasma inflammatory cytokine signature during long-term cART was distinct from acute SIV infection and resembled the inflammatory cytokine profile of uninfected aging (inflammaging) macaques. Overall, our data suggest that during cART-suppressed chronic SIV infection, dysregulation of IL-17/IL-22 cytokine effector functions and decline of Vδ2 γδT cell subsets may contribute to gut epithelial barrier disruption and development of a distinct plasma inflammatory signature characteristic of inflammaging. Our results advance the current understanding of the impact of chronic HIV/SIV infection on γδT cell functions and demonstrate that in the setting of long-term cART, the loss of epithelial barrier-protective functions of Vδ2 T cells and ensuing IEBD/MT occurs before the hallmark expansion of Vδ1 subsets and skewed Vδ2/Vδ1 ratio. Thus, our work suggests that novel therapeutic approaches toward restoring IL-17/IL-22 cytokine functions of intestinal Vδ2 T cells may be beneficial in preserving gut epithelial barrier function and reducing chronic inflammation in HIV-infected individuals.